Microbiological Profile and Inflammatory Markers in Meconium Aspiration Syndrome: Review (Asian Journal of Pharmaceutics (AJP), 2026)
Meconium aspiration syndrome (MAS) is characterized by respiratory distress in newborns exposed to meconiumstained amniotic fluid (MSAF) with no alternative explanations. Earlier, it was stated that the womb is a sterile environment and microbial colonization in neonates begins at birth. Recent studies showing the presence of microorganisms in the MSAF in utero suggest that the meconium in the fetus does contain microorganisms. These microorganisms present in MSAF and meconium may cause intrauterine infection, chorioamnionitis in mothers, neonatal sepsis, and pneumonitis in neonates. In addition, this review discusses the fetal inflammatory response to MAS. The combined involvement of obstetricians, neonatologists, and pediatricians in prevention and treatment further reduces MAS cases. Understanding the microorganisms and drug-resistant patterns in neonates with MSAF aids in diagnosing and prescribing antibiotics, which is vital in antibiotic stewardship for managing neonates with MAS.